SOCIAL-PSYCHOLOGICAL ASPECTS OF ORGANIZATION OF COMMUNICATIVE INTERACTION IN THE VIRTUAL SPACE - Sittseva, Maryna V. (Educological discourse, 2014)
In the article the analysis of the communication features of a person as a subject of virtual interaction in the socio-psychological dimension. The aim of the article is defined allocation of specific content and socio-psychological forms of communication personality in the virtual space. Based on the properties of the virtual space – transgenicе, timeless character and anonymity – the structure of socio-virtual image of man as a user of the Internet. Presents the key problems of transformation of personality under the influence of virtual social networks as a new means of communication activities. Identified threats and risks total digitalization of information flow. Considered the specific features of the person as a participant of virtual fields of social communication on the basis of which conclusions are drawn about the underdevelopment of determining the ontological, axiological and structural and functional bases of stay of the person in the Internet network, which is a promising direction of scientific-psychological study.